Whom do architects have in mind during design when users are absent? Observations from a design competition. (2016) - Verhulst, Lore; Elsen, Catherine; Heylighen, Ann
As design processes become more complex, the distance between architects and their buildings' users increases. In large-scale projects, future users often remain absent or hypothetic during design, and in some design competitions, architects are not even allowed to interact with the client. This article considers whom architects design for in such a case, and how they imagine them. Through an in-depth case study of a real-world design process, it investigates what can be learned from what architects say about whom they have in mind during design. The findings reveal a gap between how users are considered in literature versus by the architects observed. Strikingly, the term 'user' is not used at all by the latter while corporeality seems to be largely absent in how they talk about whom they design for. These findings complete Kostof's model of homunculi and contribute to a more nuanced understanding of whom architects have in mind when future users are absent or hypothetic.